Examining the impact of industry 4.0 on academic libraries - Chigwada, Josiline Phiri, 1984-; Nwaohiri, Ngozi Maria, 1972- (Emerald Publishing Limited, 2021)
As the rapid acceleration of industry 4.0 catapults a number of changes within the space of library services and operations into effect, it is more important than ever to understand the impact of technological revolutions on the academic library. This edited collection showcases the emerging issues brought by the 4th industrial revolution, and the effects on how libraries function, manage processes and continue to deliver products and services on a day to day basis. The contributing authors examine the role of the Internet of Things in the academic library, identify the nature of the emerging technologies, and investigate how these innovations might be used in academic libraries. Documenting original research which offers a fresh insight into the opportunities and challenges of a new digital world, this book also delves into the readiness of libraries and library professionals to adapt to the change and new technologies brought about by Industry 4.0. Presenting a wide-ranging road map of the future of libraries and information centres, this is an essential read for library professionals working in service delivery, as well as researchers interested in the nexus between academic libraries and emerging technologies.